2001
DOI: 10.1508/cytologia.66.189
|View full text |Cite
|
Sign up to set email alerts
|

Ploidy Levels Affect Phenotype and Cytogenetic Traits in Zea mays ssp. mays (2n=20 or 40) and Zea mays ssp. parviglumis Hybrids.

Abstract: The aim of this study was to analyse phenotype and cytogenetic behaviour of Zea mays ssp. mays and Zea mays ssp. parviglumis (Zpa) hybrids with different ploidy levels. Maize 2n =20 (Zm20) and Zpa hybrid plants (MPa20) were obtained naturally, they showed regular meiosis and fertile progeny (+80%). Otherwise, maize 2n=40 (Zm40) and Zpa hybrids (MPa30) were obtained by embryo rescue, they showed irregular meiosis and sterile progeny (0-8%). Meiotic configurations more frequently observed in the species and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
5
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…The most frequent meiotic configuration in the tri‐hybrid MDP was 5IV+10II. From this result and previous reports that support the polyploid condition of the genus Zea with the presence of two homoeologous genomes A and B (M olina and N aranjo 1987; N aranjo et al 1990; M olina and G arcía 1999, 2001; G arcía and M olina 1994) it can be suggested that the observed 5IV were the product of homoeologous chromosome pairing of A genomes from the three species.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…The most frequent meiotic configuration in the tri‐hybrid MDP was 5IV+10II. From this result and previous reports that support the polyploid condition of the genus Zea with the presence of two homoeologous genomes A and B (M olina and N aranjo 1987; N aranjo et al 1990; M olina and G arcía 1999, 2001; G arcía and M olina 1994) it can be suggested that the observed 5IV were the product of homoeologous chromosome pairing of A genomes from the three species.…”
Section: Discussionsupporting
confidence: 79%
“…From the meiotic configurations and genomic formulae of Zea species and their hybrids shown in Table 3 (M olina 1978, 1981, 1982, 1983, 1985, 1986, R osales and M olina 1984, M olina and N aranjo 1987, N aranjo et al 1990, M olina and G arcía 1999, 2001) it can be suggested: i) the 5 chromosomes of the A genome have not been significantly differentiated in the evolution of the different Zea species since they keep the ability of pairing in interspecific hybrids; ii) in interspecific Zea hybrids, B genome homoeologous chromosome pairing take place only if the respective homologous chromosomes are not present. A possible explanation of this observed pairing behavior is that mutations, variations in gene function or both events together occurred during evolution, resulting in a higher differentiation of B Zea genomes compared to A genomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations